(untitled) (The International Journal for Scientific Research, 2026)
The research aims to reveal the training needs related to teaching aids from the perspective of a sample of kindergarten teachers in several Syrian governorates, to rank those needs according to their relative importance, and to reveal the differences in them according to the following variables: (administrative affiliation of the kindergarten, academic qualifications, and years of experience). The research sample consisted of 309 teachers selected from 30 kindergartens distributed across five governorates: Damascus, Rural Damascus, Deir ez-Zor, Aleppo, and Idlib). A questionnaire consisting of 40 statements distributed evenly across four areas was used: (design of teaching aids, selection of teaching aids, use of teaching aids, and evaluation of teaching aids). The results showed that the ranking of training needs related to teaching aids was as follows: First, designing educational tools; second, employing educational tools; third, evaluating educational tools; and fourth, selecting educational tools. The results showed statistically significant differences in the kindergarten teachers’ sample’s assessment of their training needs related to teaching aids for each subfield and the overall score according to the variable of administrative affiliation of the kindergarten in favor of private sector kindergarten teachers. statistically significant differences according to the variable of academic qualification in favor of teachers with lower academic qualifications, and statistically significant differences according to the variable of years of experience in favor of teachers with fewer years of experience. The results were interpreted in light of the theoretical framework and previous studies.